PENGARUH EKSTRAK JAMU TERHADAP AKTIVITAS SEL NATURAL KILLER DALAM MELISIS ALUR SEL LEUKIMIA (K-562) SECARA IN VITRO [The Effects of Commercial “Jamu” Extracts on Natural Killer Cell Activity in Lysing Leukemic Cell Line (K-562 ) in vitro] - Fransiska R. Zakaria; Elisa Veronica D.C. (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2002)
Natural killer (NK) cell consitutes white blood cells which specifically functions in lysing tumor and virus invected cells. In this research, a commercial “Jamu” was tested to observe its effect on NK cells activity against leukemic cell lines (K562) in vitro. Jamu was extracted with hot water, diluted and added into cell cultures consisted of a mixture of human peripheric limphocyte cells, as the source of the effector NK cells, and K562 cell line i.e., the target cells which were cell line derived from human leukemia and had been labelled with H3-thymidine. The mixture of the cells were made by culturing the two cells at the ratio of 50:1 and 100 : 1, respectively. The results showed that lysing activity of NK cells in the presence of “Jamu” water extract measured as lysing percentage and lysing index increased only slightly, which were not statiscally significant. It should be considered that the test used in this research represents only a part of the lysing mechanism by NK cells against the target cells. An in vivo test for a period of time will be recessary to elucidate ffurther this NK cell activity.